Penyusunan Laporan Keuangan Sekolah Taman Kanak-Kanak Berdasarkan Pendekatan Isak 35 - Dwi Fionasari; Siti Samsiah; Wira Ramashar; Nadia Fathurrahmi Lawita; Agustiawan Agustiawan; Rudi Syaf Putra; Linda Hetri Suriyanti (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this service activity is to provide understanding to schools in terms of implementing the preparation of financial statements for Kindergarten (TK) Dewi Sartika Group 1, Kampar District, which refers to ISAK 35 regarding financial reporting of non-profit entities. This activity is carried out to help solve problems faced by managers of non-profit-based educational organizations due to their lack of understanding of accounting for financial reporting in accordance with ISAK 35. Service activities in educational organizations are carried out in several stages, starting with observations and preliminary interviews on objects activity. Then the implementation of the activity, namely by explaining the material about the basics of accounting and ISAK 35. Based on the results of this service activity, it was found that the service participants, namely nine kindergartens who were members of the Dewi Sartika Gugus 1, Kampar sub-district, began to understand and realize the importance of reporting accountability. financial statements in accordance with recommended accounting standards. Keywords: Financial Statement, ISAK 35 Abstrak Tujuan dari kegiatan pengabdian ini adalah untuk memberikan pemahaman kepada sekolah dalam hal menerapkan penyusunan laporan keuangan Taman Kanak-kanak (TK) Gugus 1 Dewi Sartika Kecamatan Kampar yang mengacu pada ISAK 35 tentang pelaporan keuangan entitas nonlaba. Kegiatan ini dilaksanakan untuk membantu menyelesaikan permasalahan yang dihadapi oleh pengelola organisasi pendidikan berbasis nonlaba atas kurang paham nya tentang akuntansi untuk pelaporan keuangan yang sesuai dengan ISAK 35. Kegiatan pengabdian pada organisasi pendidikan ini dilakukan dengan beberapa tahapan, dimulai dengan melakukan observasi dan wawancara pendahuluan pada objek kegiatan. Kemudian pelaksanaan kegiatan, yaitu dengan menjelaskan materi tentang dasar-dasar akuntansi dan ISAK 35. Berdasarkan hasil dari kegiatan pengabdian ini diketahu bahwa peserta pengabdian yaitu sembilan TK yang tergabung dalam Gugus 1 Dewi sartika kecamatan kampar, mulai memahami dan menyadari arti penting dari pertanggungjawaban pembuatan laporan keuangan sesuai dengan standar akuntansi yang dianjurkan. Kata kunci: Laporna Keuangan, ISAK 35